P37 Correlation of emPHasis-10 with clinical tests: insights from the ASPIRE registry. (11th November 2022) - Alabed, S; Dwivedi, K; Durrington, C; Alandajani, F; Condliffe, R; Elliot, C; Charalampopoulos, A; Hameed, A; Thompson, R; Rothman, A; Armstrong, I; Swift, AJ; et al.
Abstract : Introduction: EmPHasis-10 (E10) assesses health-related quality of life in patients with pulmonary arterial hypertension (PAH) and is an independent prognostic marker. We aimed to assess E10 score correlations with functional capacity, pulmonary hemodynamic, and cardiac MRI parameters (CMR). Methods: Consecutive PAH patients with E10 between 2014 and 2020 were identified from the ASPIRE registry. The correlation between E10 and investigations performed within 30 days was assessed using Spearman's correlation coefficient. Subgroup analysis was performed in patients with idiopathic PAH (IPAH) and PAH associated with connective tissue disease (PAH-CTD). Results: 1801 patients aged 59±26 years were included, 25% had IPAH and 36% CTD-PAH, 56% were treatment-naive, 70% women, and 80% in WHO functional class 3. The mean E10 score was 29±13. Moderate correlations with incremental shuttle walking test distance (r=-.47, n=1505) and weak correlation with n-terminal pro-b-type natriuretic peptide (r=.39, n=94), WHO functional class (r=.33, n=1792), right heart catheter parameters (pulmonary vascular resistance r=.31, n=442) and percent predicted TLco (r=-.25, n=817) were observed ( table 1 ). CMR parameters demonstrated weak-poor correlations with E10 (r=.15-.26), higher in IPAH and CTD-PAH subgroups than in the overall cohort. Conclusion: Despite being an independent prognostic factor, E10 score correlates only moderately with exercise capacity and weakly with hemodynamics, pulmonary function and CMR parameters. This study further highlights the unique added value of the E10 test considering the lack of a clinical surrogate marker that strongly reflects how a patient feels and how their life is affected by PAH.